Decision Support System of The Zakat-Mal Distribution Based On The Poor Indicators - Samsudin, Samsudin; Ilyas, Ilyas; Panca Nuari, Trafo Lajusi (Kopertis Wilayah X)
A Decision Support Software has diplaning, analyzed, designed, tested and implemented, Sofware goal is to simplify the User in Zakat Mal Distributed in Kab. Downstream Indaragiri. People who receive zakat mal is one group received it (poor and needy) criteria, Fixed income, number of dependents, Frequency of food, Asset Ownership, type of dwelling. To Make Decision Support Software Using Waterfall Model consisting of several phases, namely: Planing, Analysis, Design, Testing and Implementation. In Analyzing Data Using Fuzzy MADM (Multiple Attribute Decision Making) with Simple Additive weighting method (SAW). In the Feasibility Testing Software Decision Support System Using use you Pre and Post Test System Using this with T. After the system was tested to conclude there is a difference between the pre and post use. And the probability of 0,037 <0.05 between pre- and post proves there is a difference significantly (significant).